Extractive Spectrophotometric Methods for the Determination of Amlodipine Besylate - Murthy, T.K.; Reddy, M.N.; Dharma Reddy, M.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
Two simple and sensitive extractive spectrophotometric methods (Methods A and B) have been developed for the determination of amlodipine besylate (ADB) in bulk samples and pharmaceutical preparations. It forms green coloured complex with fast green FCF exhibiting maximum absorption at 625 nm (Method A). In Method B, ADB forms yellowish orange coloured complex with orange II showing maximum absorption at 485 nm. Both the methods obeyed Beer's law limits in the concentration range of 2.5 to 20 μg/mL of ADB.